2015
DOI: 10.1016/j.cbi.2014.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Aldose reductase inhibition alleviates hyperglycemic effects on human retinal pigment epithelial cells

Abstract: Chronic hyperglycemia is an important risk factor involved in the onset and progression of diabetic retinopathy (DR). Among other effectors, aldose reductase (AR) has been linked to the pathogenesis of this degenerative disease. The purpose of this study was to investigate whether the novel AR inhibitor, beta-glucogallin (BGG), can offer protection against various hyperglycemia-induced abnormalities in human adult retinal pigment epithelia (ARPE-19) cells. AR is an enzyme that contributes to cellular stress by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 55 publications
1
36
0
Order By: Relevance
“…Although osmotic stress also resulted in an increase in oxidative stress, it did not reach significant levels. This may be mediated, in part, through uptake of D-glucose, but not L-glucose, by RPE cells and enhanced aldose reductase activity (13). However, the increased oxidative stress in RPE cells was not associated with changes in oxidative response genes, including NRF2 and its downstream effectors HO-1 and Prdx2.…”
Section: Discussionmentioning
confidence: 88%
“…Although osmotic stress also resulted in an increase in oxidative stress, it did not reach significant levels. This may be mediated, in part, through uptake of D-glucose, but not L-glucose, by RPE cells and enhanced aldose reductase activity (13). However, the increased oxidative stress in RPE cells was not associated with changes in oxidative response genes, including NRF2 and its downstream effectors HO-1 and Prdx2.…”
Section: Discussionmentioning
confidence: 88%
“…10 A positive correlation between hyperglycemia and AR expression has been observed in many studies 11,12 and shows that AR activation plays a key role in diabetic cataract (DC) formation. 13,14 Indeed, diabetes-dependent increases in AR activity can be found in lenses of a rat model of diabetic cataract.…”
mentioning
confidence: 87%
“…23,24 Our previous studies indicated that genetic ablation or pharmacological inhibition of AR reduced inflammatory responses in the eye 20,21 and prevented retinal pigment epithelial (RPE) cell death under hyperglycemic conditions. 11 As a result of these observations, blockade of AR appears to be a strategy for prevention of a variety of ocular diseases. Unfortunately, previous clinical trials of ARIs have been unsuccessful due to toxicity and side effects related to poor specificity.…”
mentioning
confidence: 99%
“…Recent studies also implicate AR in the pathogenesis of uveitis [2527] and fibrotic changes associated with posterior capsular opacification [28, 29]. Genetic or pharmacological blockade of AR successfully alleviates inflammatory responses induced by endotoxin [25, 26, 3032] or hyperglycemia [3335]. Our previous study showed that genetic or pharmacological downregulation of AR prevents endotoxin-induced inflammatory responses in RMG primary cell cultures [26].…”
Section: Introductionmentioning
confidence: 99%